Traditional water installations and their tourism employment in Tunisia, the path of Hanaya water - from Zaghouan to Carthage as a model - - Fadel HANI (Social Sciences Journal, 1970)
The problem of this research allows studying the role of traditional hydraulic techniques inthe diversification of the tourist offer and the interest of cultural tourism for the conservation,valuation of this hydraulic heritage and realization of tourism development at the economic, socialand cultural in the water circuit of Zaghouan to Carthage, which was created in the last years.This presidential project aims to revive the historical memory of the stream of Zaghouan toCarthage and the valuation of environmental and archaeological sites.In spite of the developmentof certain areas such as the temple of the water, the creation of a national park and an urban parkin Zaghouan, the preservation of some historic monuments, the improvement infrastructure andaccessibility of some sites, the tourism promotion in this circuit is insufficient. The circuit aqueductis tourism of passage, in low impact on the local and regional development. The conservation ofmonuments is difficult and expensive.The development of ecotourism tourism in the circuitaqueduct requires consideration of ecological and economic dimensions and the preservation ofcultural identity and interests of local communities for sustainable tourism development. Theparticipation of the local populations in the valuation and development of this hydraulic heritage isnecessary.